Synthesis of Several Bisabolane Type Sesquiterpenoids from Xanthorrhizol - M.H, Ngai,; H.M, Sirat (Malaysian Journal of Science, 2005)
R-(-)-Xanthorrhizol 1, the main constituent of Curcuma xanthorrhiza, has been shown to possess interesting biological activities, including antibacterial, antifungal, antitumour and antioxidant activities. Xanthorrhizol was isolated from the essential oil of C. xanthorrhiza in 39% yield by vacuum column chromatography. Curcuhydroquinone 2, an antibacterial compound isolated from the Caribbean gorgonian coral, Pseudopterogorgia rigida has been synthesised in two steps from xanthorrhizol. Xanthorrhizol has also been converted to 10R- and 10S-10,11-dihydro-10,11-dihydroxyxanthorrhizols 3 and 4, a bisabolane type sesquiterpenoid isolated from Iostephane heterophylla, using Sharpless asymmetric dihydroxylation as the key step.